2004
DOI: 10.2134/agronj2004.0001
|View full text |Cite
|
Sign up to set email alerts
|

Crop and Soil Productivity Response to Corn Residue Removal

Abstract: of greenhouse gases in the atmosphere (IPCC, 2001), and ability of our agricultural systems to sustain produc-Society is facing three related issues: overreliance on imported fuel, tion at rates needed to feed a growing world population increasing levels of greenhouse gases in the atmosphere, and producing sufficient food for a growing world population. The U.S. De-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
391
3
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 530 publications
(401 citation statements)
references
References 103 publications
(195 reference statements)
6
391
3
1
Order By: Relevance
“…Regarding the nitrogen levels maximum number of plants (7.84 m 2 ) were observed in the plots where 200 kg•ha −1 (N 2 ) were applied followed by the plot treated with 300 kg•ha −1 (N 3 ) and the minimum number of plants (7.35 m 2 ) were observed in (N 1 ) where minimum nitrogen 100 kg ha −1 were applied. These results are in line to [17] who reported that tillage systems greatly affected maize germination, its growth and development.…”
Section: Resultssupporting
confidence: 92%
“…Regarding the nitrogen levels maximum number of plants (7.84 m 2 ) were observed in the plots where 200 kg•ha −1 (N 2 ) were applied followed by the plot treated with 300 kg•ha −1 (N 3 ) and the minimum number of plants (7.35 m 2 ) were observed in (N 1 ) where minimum nitrogen 100 kg ha −1 were applied. These results are in line to [17] who reported that tillage systems greatly affected maize germination, its growth and development.…”
Section: Resultssupporting
confidence: 92%
“…Adverse effects of excessive corn stover harvest on soil structure and physical quality have been expected and documented by several authors (e.g., Wilhelm et al, 2004;Lal, 2007, 2009a). Therefore, the impacts of corn stover harvest and various tillage practices on soil physical quality for crop production should be assessed using properties or processes that can quantify the physical stresses being imposed on crops by various soils (da Silva and Kay, 2004).…”
Section: Introductionmentioning
confidence: 92%
“…More detailed discussions of potential impacts of stover removal on future productivity and soil quality are presented by Wilhelm et al [16], Wilts et al [17], and Kim and Dale [18]. Understanding this component of biomass removal, including the additional plant nutrients that will be removed and have to be replaced, is very important for the long-term success of the bio-energy system.…”
Section: Article In Pressmentioning
confidence: 99%